A case of refractary epilepsy and related pain due to dysmenorrhea solved with loading dose of lacosamide: clinical and neurophysiological correlates - Marchitto, Nicolino; Ceratti, Umberto; Dalmaso, Serenella; Raimondi, Gianfranco (Acta Biomedica Atenei Parmensis, 2017)
In most cases, the etiology of epilepsy is unknown, although some individuals may develop epilepsy as a result of certain brain injuries, following a stroke, a brain tumor or because of drugs and alcohol. Even some rare genetic mutations may be related to the onset of the condition. Seizures are the result of excessive and abnormal activity of neurons in the cerebral cortex. In this case report we show a clinical case of refractory epilepsy due to pain related to uncontrolled dysmenorrhea. The patient, 43 yrs old, had a history of epilepsy of 20 years and ovarian cancer. She was treated with lamotrigine, clonazepam and levomepromazina maleato. At admission the patient shew seizures due to pain related to dysmenorrhea. In emergency we treated with verapamil hydrochloride 10 mg ev, subsequently verapamil hydrochloride 20 mg in 250 ml of saline solution as maintenance dose. Then we decided to administer a loading dose of 100 mg cpr of Lacosamide to stop the treatment with verapamil hydrochloride. With Lacosamide we solved the seizures in 24 hours.